Waktu Layar Gawai dengan Tingkat Kecemasan Anak - Nova Lina Langingi; Citra Stevani Kondoj; Grace Fresania Kaparang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the relationship between screen time and anxiety levels in children in East Lansot Tareran Village, North Sulawesi Province. The method used is a cross-sectional design with the formula frequency, percentage and Spearman rho. The sampling technique in this study was purposive sampling, with the total number of participants being 30 children. Data collection using the Spence Children's Anxiety Scale (SCAS) questionnaire. The results showed that as many as 43.3% of the child participants used 4-6 hours of screen time on their devices and the children who experienced an overall increase in anxiety were 43.3%. The results of the Spearman's rho statistical test found that SCAS had a p-value of .046 with r = .367. Furthermore, the obsessive-compulsive disorder (OCD) subscale analysis showed the value of p = .005 with r = .500. In conclusion, there is a significant weak relationship between screen time and anxiety levels and the higher screen time, the higher the child's anxiety level. Furthermore, there is a significant moderate relationship between screen time and OCD and the higher screen time, the higher the increase in OCD. Keywords: Children, Anxiety, Screen Time